(untitled) (Revista de Ciências Agroveterinárias, 2019)
The objective of this work was to evaluate the adjustment of taper models with and without bark for clone GG100 in a commercial plantation located in the southern state of Tocantins. Twenty-five trees were cubed in which data were fitted five taper models, three of which were the most used in Brazil and two representing the poorly tested models in the country. In the evaluation of the taper models, the following statistical criteria were adopted: standard error of the estimate, adjusted coefficient of determination, mean deviation, sum of squares of the relative residue, percentage residue, and analysis of the distribution of residues. It was concluded by an exponent-shape type model to describe the trunk profile with and without bark of individual clones of clone GG100.